2017
DOI: 10.1016/j.diii.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of ovarian vein for pelvic congestion syndrome with ethylene vinyl alcohol copolymer (Onyx®)

Abstract: Pelvic embolization using ethylene vinyl alcohol copolymer (Onyx) has a favorable clinical success for pelvic congestion syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…Non-adhesive embolic fluids are most commonly used in the arterial district, but, in some specific settings, they can also be used in the venous district. The scientific paper with the largest series of vein embolization with non-adhesive embolic fluid was published by Marcelin et al [ 66 ], who demonstrated that the use of Onyx to treat female pelvic varicoceles is an effective and safe approach. Marcelin stated that, in the venous district, these fluids have the great advantage over coils and sclerosing fluids of having good release control, the possibility to see how they distribute on fluoroscopy and both reduced risk of revascularization of the treated venous axis and of dangerous migration toward central venous system.…”
Section: Venous Embolizationmentioning
confidence: 99%
“…Non-adhesive embolic fluids are most commonly used in the arterial district, but, in some specific settings, they can also be used in the venous district. The scientific paper with the largest series of vein embolization with non-adhesive embolic fluid was published by Marcelin et al [ 66 ], who demonstrated that the use of Onyx to treat female pelvic varicoceles is an effective and safe approach. Marcelin stated that, in the venous district, these fluids have the great advantage over coils and sclerosing fluids of having good release control, the possibility to see how they distribute on fluoroscopy and both reduced risk of revascularization of the treated venous axis and of dangerous migration toward central venous system.…”
Section: Venous Embolizationmentioning
confidence: 99%
“…In a study evaluating vascular plugs, despite the advantage of less exposure to radiation, no significant difference was found in clinical success and improvement in 1-year follow-up results. In patients who underwent embolization with ethylene vinyl alcohol copolymer material, a success rate of 76.4 % was observed and no complications were found [20].…”
Section: Endovascular Treatmentmentioning
confidence: 85%
“…Embolic materials include coils, Gelfoam slurry, STS, and more recently ethylene vinyl alcohol copolymer or Onyx. 28,31 The combination of different techniques and utilization of various embolic materials across these studies begs the question of what is the optimal technique to employ based on patient characteristics and is an ongoing research question.…”
Section: Discussionmentioning
confidence: 99%